ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU HIDUP SEHAT WANITA PEKERJA SEKS TERHADAP UPAYA PENCEGAHAN IMS - HIV/AIDS DI RESOSIALISASI TEGALREJO - UNGARAN - Widjanarko Heru, Tri Sakti Widyaningsih, (STIKES Widya Husada Semarang, 2010)
âAnalysis Factors Correlation of Behavior Live Healthy Woman Sex Worker about Effort Prevention of IMS-HIV/AIDS in Tegalrejo Prostitution-UngaranâMany barrier factors effort prevention and tackling of epidemic HIV/AIDS in total case although broad distributing more and more increase in Indonesia has already beginning systematic since 1994. Economic trouble add total their risk activity, at serious condition cause half of them are young lady unuseful, at least woman sex worker for the last choice. While effort prevention spreading of IMS not yet show the result make happy, now spreading of HIV and AIDS on their circle so big and fast. This study uses an analytic descriptive methode with cross sectional approach and rank spearment correlation test. Purposes getting the frequency distribution from searching variable and correlation possibility.Â Removal of respondence are doing by accidental sampling in Tegalrejo prostitution Ungaran city with inclusive category : woman with 15-35 years old, work for woman sex worker between one month and one year, can read and write, prepare for respondence, and woman sex worker was not yet exposed IMS and HIV/AIDS. The result of research conclude that age factor, educational level, knowledge, attitude and outreach program have correlation with behavior live healthy the woman sex worker in Tegalrejo prostitution Ungaran city, that each factors show positive correlation (p value < 0.05). From many variables opinion that influence behavior live healthy woman sex worker, suggestion for the next research can be detected more another factors of them. Â Keywords : Behavior live healthy, women sex worker, prevention of IMS-HIV/AIDS.